Tendencies of the accentuation of polysyllabic nouns of the West Aukštaitian of Kaunas in the written sources of the 1950s and 1960s - Ragaišienė, Vilija (Lietuvių kalba, 2019)
The article analyses the dialectal material collected in the area of the West Aukštaitian of the Kaunas subdialect in the written sources of the 1950s and 1960s at the Dialect Archive of the Geolinguistic Centre of the Institute of the Lithuanian Language. Based on the data of the written sources, the goal is to describe the accentuation peculiarities of the polysyllabic nouns of the West Aukštaitian of the Kaunas subdialect in the written sources of that time, to discuss their accent models and to establish the accentuation tendencies of this subdialect. After the research was completed it was established that there is a tendency in the West Aukštaitian of the Kaunas subdialect to stress polysyllabic suffixed nouns according to three accentual models: 1) fixed, 2) mobile and 3) fixed-mobile. The author of the article is of the opinion that the accentual variance of parallel derivatives with suffixes could have been determined not by one factor, but by a set of factors. The appearance of accentual variants is linked to semantics, the accentual and semantic model of two plurals, the accentual variance of the root words, the soft ending of the stem of words and is explained by the stress analogy of the same type of word formation. The author surmises that the phenomena of oxytogenesis and baritogenesis in the subdialect under research could have worked by the principle of structure. The accentuation of some suffixes (e.g., -iena and -ėja) can demonstrate the change of the accentual models in the Aukštaitian subdialect – the movement of the mobile accentuation model from the South Aukštaitian subdialect in the direction of the North.